The Effect of Fine-Grained Control of Workflow on Informal Learning: The Mediating Effect of Teacher Burnout. (13th June 2022) - Lu, Zenghui; Chen, Yanning
Abstract : Workflow fine control is an important research tool for the mediating effect of teacher burnout. Based on the fine control theory of workflow, this paper constructs a mediating effect model of teacher burnout in primary and secondary school teachers from the perspective of informal learning. The model designs a measurement scale based on the results of fine control, and the scale is revised through informal learning pretests to form the logical frame analysis loop of this paper. The scale uses Likert 5-point scoring, from 1.5 to represent never, rarely, occasionally, often, and always, which solves the difficulty of quantitative analysis of teacher burnout data. During the simulation process, SPSS 20.0 and AMOS 7.0 were used to conduct empirical analysis, exploratory factor analysis and confirmatory factor analysis on the survey data, and the measurement scales were tested. The empirical analysis results show that this paper uses cluster sampling and random sampling to carry out a questionnaire survey on 1022 primary and secondary school teachers. The measurement scale includes 19 items. Through exploratory factor analysis and confirmatory factor analysis, the control method is determined. In two dimensions, the revised control style questionnaire has a reliability of 0.951, and items with factor loadings less than 0.5 are eliminated, which effectively improves the control performance of informal learning.